Buenas prácticas de enfermería en la prevención de neumonías asociadas a la ventilación mecánica en hospitales de tercer nivel de América Latina - Sánchez Estrada, Indira Anabel (2025)
Ventilator-Associated Pneumonia (VAP) is the most prevalent nosocomial infection in Intensive Care Units (ICU). Good nursing practices are essential for its prevention. Objective: to conduct a systematic review of good nursing practices in the prevention of nosocomial infections associated with mechanical ventilation, and to evaluate the effectiveness of its implementation in third-level hospitals in Latin America. Methodology: a systematic review of studies published between 2019 and 2024 was conducted. The search process was conducted in the Scielo, LILACS and Redalyc databases and allowed the selection of 10 articles from 6 Latin American countries, whose samples were pediatric patients, adults, and older adults. Results: a package of interventions is applied in pediatric patients that emphasizes maintaining oral hygiene and raising the head of the bed. These interventions are also conceived for adult and older adult patients. In studies in the adult population, although full adherence to the implemented interventions is not achieved, a reduction in the risk of pneumonia and in the length of hospital stay is observed. Conclusions: the nursing intervention packages, which are applied in the ICUs of Latin America, in the care of patients with VAP, coincide in including as main nursing care actions, oral hygiene measures, elevation of the head of the bed and observance of protocols for endotracheal aspiration. General Area of Study: Medicine. Specific area of study: Intensive care unit. Type of study: Bibliography Review.